Meningkatkan Kualitas Pembelajaran Azan Dan Iqamah Melalui Metode Demonstrasi Pada Siswa Kelas II MI Al-Mukminin Kalangan Perak Jombang - Afifah Roziah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Articles This is the result of Research Action Class (PTK), which are specifically discussed the improvement of the quality of the results of learning materials azan and iqamah in the eyes of subjects Jurisprudence through method demonstrations . Taking locus in MI Al Mukminin Among District of Perak District Jombang , research is going to answer questions about how the method of demonstration in improving the quality of the results of learning azan and iqamah p there 's ISWA Class II MI Al- Mukminin Among Perak Jombang . Using the observation method in several cycles , this study found that the use of the demonstration method was effective in improving the learning outcomes of fiqh subjects with the azan and iqamah material for class II students at MI Al- Mukminin Perak Jombang . Research this jug a finding that learning by using the method of demonstration to optimize repetition lafaz azan by teachers and quoted repeatedly by the student until the student memorized and eloquent in pronouncing lafaz azan and iqamah and use video media as media support can be applied to the eyes of subjects and principal another discussion .